Rising to the Challenge: Reflections on a Round of Pandemic Bargaining - Savage, Larry (Academic Matters, 2020)
Bargaining is an intensive and complex procoess during the best of times, but what happened when the Brock University Faculty Association found itself bargaining a new collective agreement in the middle of a pandemic? --Editor's note